2011
DOI: 10.1007/s10072-011-0757-3
|View full text |Cite
|
Sign up to set email alerts
|

Cough headache secondary to spontaneous intracranial hypotension complicated by cerebral venous thrombosis

Abstract: Cough headache may be the clinical manifestation, sometimes isolated, of an intracranial disease. There are several possible causes of secondary cough headache. The hypothesis that cough headache may be the expression of spontaneous intracranial hypotension has been advanced only recently. In fact, this would represent an exception to the rule that cough headache is generally secondary to conditions leading to an increase in intracranial pressure and/or volume. We report and discuss a case of cough headache se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The venous engorgement leads to the appearance of a thickened dura and the dilation of cerebral veins and sinuses, resulting in a decrease in blood flow velocity. Studies using transcranial Doppler ultrasound have shown that blood flow velocities in the sagittal venous sinus decrease by about 47% post-lumbar puncture (LP) [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The venous engorgement leads to the appearance of a thickened dura and the dilation of cerebral veins and sinuses, resulting in a decrease in blood flow velocity. Studies using transcranial Doppler ultrasound have shown that blood flow velocities in the sagittal venous sinus decrease by about 47% post-lumbar puncture (LP) [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, because he developed a headache 26 days later, we hypothesized the following: At the time of the procedure, a small hole was created when the needle grazed the dura, where the CSF leak may have become severe enough to cause hypotension for 26 days. Another possibility is that the part of the dura that was weakened by needle grazing was torn by a minor event that increased the CSF pressure, such as coughing or sneezing [ 13 ]. Therefore, based on the patient's symptoms, MRI findings, and history of spinal pain procedure, our impression of the patient's headache was secondary intracranial hypotension, which was considered highly correlated with the pain intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely they may present with headache that is non-postural [18,19] paradoxically caused by lying down [20] or intermittently triggered by coitus [9], cough [21], head movements [22] or various forms of exertion [23]. The headache may be associated with nausea or emesis, neck stiffness and cochlear-vestibular signs commonly [2,5,[24][25][26] or with facial numbness, pain or weakness and dysgeusia less commonly [27].…”
Section: Clinical Findingsmentioning
confidence: 99%